2007
DOI: 10.1080/14685240600833094
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulations of high velocity ratio coaxial jets: mixing properties and influence of upstream conditions

Abstract: Direct numerical simulations (DNS) are performed to investigate mixing in free round coaxial jets. A great attention has been put on the influence of upstream conditions upon the global flow structure and the mixing process. The mixing behavior is studied through the spatial and temporal development of the mixture fraction of the annular and the inner fluids, and examined by means of flow visualization and statistics. It is shown that the turbulent mixing process and the mixture fraction field in coaxial jets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(44 reference statements)
2
21
0
Order By: Relevance
“…As in plane mixing layers 11 and single jets, 12 the coaxial jets develop counter-rotating pairs of streamwise vortices stretched between consecutive vortex rings: these play a major role in the mixing process. Indeed, in a recent numerical study, 13 we have shown that the ejections of the species seeded in the outer jet associated with these streamwise vortices strongly enhanced the jet mixing properties. Balarac et al 13 also demonstrated that the turbulent mixing process is strongly affected by the jet upstream conditions, which modify the transitional state.…”
Section: Introductionmentioning
confidence: 81%
“…As in plane mixing layers 11 and single jets, 12 the coaxial jets develop counter-rotating pairs of streamwise vortices stretched between consecutive vortex rings: these play a major role in the mixing process. Indeed, in a recent numerical study, 13 we have shown that the ejections of the species seeded in the outer jet associated with these streamwise vortices strongly enhanced the jet mixing properties. Balarac et al 13 also demonstrated that the turbulent mixing process is strongly affected by the jet upstream conditions, which modify the transitional state.…”
Section: Introductionmentioning
confidence: 81%
“…Stanley et al [13], Reichert and Biringen [14] did DNS of a compressible plane jet exhausting into a parallel stream. Balarac et al [15,16] performed DNS of coaxial jet at moderate Reynolds with high velocity ratio.…”
mentioning
confidence: 99%
“…The introduction of white noise perturbation avoids difficulties in specifying random perturbation with a given spectrum; this region is not representative for confrontation to experimental investigations as the causes of disturbances is linked to several sources like vibrations, pressure waves… However, it has been shown [3,4,21] that the consideration of hyperbolic profile let to develop easily the main instabilities and the flow features.…”
Section: Resultsmentioning
confidence: 99%